Epitope mapping of recombinant Salmonella enterica serotype Heidelberg flagellar hook-associated protein by in silico and in vivo approaches - Hung-Yueh Yeh (BMC Veterinary Research)
Abstract Background Salmonella is a leading cause of human acute bacterial gastroenteritis worldwide. Outbreaks of human salmonellosis have often been associated with consumption of contaminated poultry products. Various strategies have been explored to control this microorganism during poultry production and processing. Vaccination of broiler chickens is regarded as one of the effectives means to control this microorganism. The aim of the present study was to compare the epitope identification in the Salmonella enterica serotype Heidelberg FlgK protein by in silico prediction and in vivo experiment with mass spectrometry in association with immunoprecipitation proteomics. Results The Salmonella serotype Heidelberg FlgK protein contains 553 amino acids with a molecular mass of 61 kDa. This protein is conserved among Salmonella serotype Heidelberg isolates. The results show that both approaches identified three common shared consensus peptide epitope sequences at the positions of 77–95, 243–255 and 358–373 in the Salmonella serotype Heidelberg FlgK protein. Conclusions These findings provide a rational for further evaluation of these shared linear epitopes in vaccine development to cover the chicken population.